The graph of the line with the given slope that passes through (-3, 3) is shown in the image attached below.
<h3>What is the Equation of a Line in Slope-intercept Form?</h3>
The equation in slope-intercept form of a line, is y = mx + b, where:
b = y-intercept
m = slope = change in y/change in x.
Given a line with slope = 2 and passes through (-3, 3), plug in m = 2 and (a, b) = (-3, 3) into y - b = m(x - a) to write the equation of the line
y - 3 = 2(x - (-3))
Rewrite in slope-intercept form
y - 3 = 2x + 6
y = 2x + 6 - 3
y = 2x + 3
Therefore, the graph of the line with the given slope that passes through (-3, 3) is shown in the image attached below.
Learn more about slope-intercept form on:
brainly.com/question/1884491
1.
1=87 corresponding angle.
2=180-87=93
2.
1=78 corresponding angles
2=78 verticle angles
3.
Set it up as (6x - 11) = 37
37 + 11 =48
6x = 48
x = 8
4.
Take 142 and see that it is supplementary to angle 2 so 180-142 = 38
38 is corresponding to the equation 2(x + 9)
So 2(x + 9) =38
Distributive property
2x + 18 = 38
38-18=20
2x =20
x = 10
Angle 2 is equal to 38 from supplementary to 142
I’m pretty positive about 1-3 but 4 maybe not be correct. But most likely these are correct
6,000 times 6,000 ten times or 6,000 times 6,000 squared maybe I'm not entirely sure sorry
x = 4
x = -1
x = 0
Equation at the end of step 1 :
((3 • (x3)) - 32x2) - 12x = 0
Step 2 :
Equation at the end of step 2 :
(3x3 - 32x2) - 12x = 0
Step 3 :
Step 4 :
Pulling out like terms :
4.1 Pull out like factors :
3x3 - 9x2 - 12x = 3x • (x2 - 3x - 4)
Trying to factor by splitting the middle term
4.2 Factoring x2 - 3x - 4
The first term is, x2 its coefficient is 1 .
The middle term is, -3x its coefficient is -3 .
The last term, "the constant", is -4
Step-1 : Multiply the coefficient of the first term by the constant 1 • -4 = -4
Step-2 : Find two factors of -4 whose sum equals the coefficient of the middle term, which is -3 .
-4 + 1 = -3 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -4 and 1
x2 - 4x + 1x - 4
Step-4 : Add up the first 2 terms, pulling out like factors :
x • (x-4)
Add up the last 2 terms, pulling out common factors :
1 • (x-4)
Step-5 : Add up the four terms of step 4 :
(x+1) • (x-4)
Which is the desired factorization
Answer:
aint no way :)))
Step-by-step explanation: